Determination of Peroxide Value in the Plastic Resin - Luo, Chuan; Wu, Beilei; Lin, Zhenxin; Yuan, Lifeng; Wang, Hao (Asian Journal of Chemistry, 2013)
The peroxide value of polyethylene, polypropylene and polystyrene resin was detected by titration method, Plastic particles were dissolved in a mixed solvent of chloroform and acetic acid (2:3, volume ratio), add 0.5 mL of saturated potassium iodide solution, shake for exactly 1 min then add 30 mL of water, titrated with 0.01 mol L-1 sodium thiosulphate. The detection limit of the method reaches 0.05 mmol L-1. The relative standard deviations were below 9.5 %. The method was effectively applied for the determination of peroxide value in plastic particles.